To revisit or not to revisit Beijing: The role of destination image - Che Ha, N.; Farinda, A.G.; Zhou, J. (2008)
This study examines the effects of destination image on the future intention of tourists to visit (or not to visit) Beijing. Ten dimensions are used to measure the destination image:landscape and surroundings, cultural attraction, nightlife and recreation, shopping, sports, accommodation, gastronomy, price and cost, transportation, social interaction and friendliness. The study is also to explore the important factor(s) that contribute to the explanation of relationship.